The Effects of Treatment of Korean Medicine for Superior Labrum Anterior to Posterior Lesions: A Retrospective Chart Review - Ju-Hun Park; Hyun-Woo Cho; Han-Bin Park; Dong-Hwi Yoo; Sang-Gyun Kim; Oh-Hoon Kwon; Kang-Eah Choi; Seong-Hun Choi; Hong-Min Chu; Jong-Won Jang (MEDrang Inc., 2020)
Background This study aimed to investigate the clinical effectiveness of treatment of Korean medicine on superior labrum anterior to posterior (SLAP) lesions. Methods A total of 55 inpatients diagnosed with SLAP lesions by magnetic resonance imaging, were investigated from May 1st, 2014 to May 31st, 2019 at Haeundae Jaseng Hospital of Korean Medicine. The patients were sorted by gender, age, causing factor, illness duration, period of hospitalization, SLAP lesion type, complications, and treatments. Treatments included acupuncture, pharmacopuncture, Chuna therapy, herbal treatment, and physiotherapy. After treatment, the Numeric Rating Scale, Shoulder Pain and Disability Index, and European Quality of Life 5-Dimension questionnaire were used to evaluate treatment effect. Results There were more males than females in this study (1:0.83). Patients were more likely to be in their 50s (38.18%), have an unknown etiology (70.91%), and be in the subacute disease stage (41.82%). According to the SLAP lesion type, most of the inpatients had Type 2 lesions (69.09%). For inpatients diagnosed with SLAP lesions, the mean shoulder numeric rating scale score decreased from 5.55 ± 0.90, to 4.07 ± 1.18 (p < 0.001), the mean Shoulder Pain and Disability Index score decreased from 50.35 ± 18.36, to 39.90 ± 19.34 (p < 0.001), and the mean European quality of life 5-dimension index increased from 0.70 ± 0.16, to 0.75 ± 0.13 (p < 0.01) after treatment. Conclusions Treatment of Korean medicine effectively decreased pain and increased the quality of life of the patients with SLAP lesions in this study.